Lateral Extra-Articular Tenodesis Reduces the Rate of Revision Anterior Cruciate Ligament Reconstruction in Elite Athletes. Issue 7 (30th July 2021) - Balendra, Ganesh; Willinger, Lukas; Jones, Mary; Williams, Andy; Borque, Kyle
Objectives: Lateral extra-articular tenodesis (LET) has been shown to decrease the re-rupture rates in cases of ACL reconstruction (ACLR) at high risk of failure when combined with hamstring (HS) autograft ACLR. The effects of LET have never been evaluated in elite athletes and have only sparingly been assessed when combined with bone-patellar tendon-bone (BTB) ACLR. The purpose of this study was to assess the efficacy and safety of the addition of a LET. Methods: A retrospective consecutive series of elite athletes who underwent primary ACL reconstruction by the senior author during the period of January 2005 to June 2018 were evaluated. An elite athlete was defined as one who is either paid or participates in national or international level competition in their sport. The primary outcome measure was undergoing revision ACLR, while the secondary outcome was the need for any further operative procedure. Chi square test was used to determine differences and statistical significance was defined as p < 0.05. Results: 456 elite athletes underwent ACLR during this time period. Overall 9.1% (31 of 339) underwent revision ACLR. In the ACLR + LET group, 3.4% (4 of 117) underwent ACLR revision (relative risk reduction [RRR], 0.626, p = 0.045) (table 1). Subgroup analysis by graft type yielded similar ratios, but did not reach statistical significance (Tables 2 and 3). There was no difference in re-operation rates between the ACLR alone and ACLR + LET groups (33.9% vs 30.7%, p = 0.531). Conclusions: The addition of a LET significantly reduced the rate of revision ACLR in elite athletes and did not increase the rate of subsequent operations.